Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Revenge Porn dalam Perspektif Hukum Pidana Islam - Kamarul Hidayat; Syofiaty Lubis (UNES Law Review, 2023)
Criminal acts continue to develop along with developments in time and technology, but the law does not keep up with these developments, ultimately creating legal loopholes or the irrelevance of the law to criminal acts. In this study, the approach used is a normative juridical approach. The normative juridical approach is a legal research method that involves analysis of library material or secondary data as the main source to be researched through investigation of regulations and literature related to the issue being investigated. Based on the results of the study, the criminal act of revenge porn based on a judge's decision is prohibited in Islamic criminal law because of the act of adultery and bringing oneself closer to adultery and spreading disgrace with punishments of stoning and whipping as well as ta'zir.